The transfer of undertakings with specific reference to the transfer of insolvent undertakings - an evolution of the South African law - Spree, Wolfgang (Stellenbosch : University of Stellenbosch, 2007)
Thesis (LLM (Mercantile Law))--University of Stellenbosch, 2007.